Study of Support and Services Provided by Business Incubators in Entrepreneurship - Siddiqui, Daniya; Ahmad, Naseeb (AMC Indian Journal of Entrepreneurship, 2022)
Entrepreneurship is regarded as a critical element of economic system and it contributes significantly to economic development, employment generation, poverty alleviation, and wealth creation. The Indian government is aggressively promoting innovative startups and entrepreneurship while allocating large sums of money to foster entrepreneurship development. This research paper attempted to quantify the services made available by incubators in the development of entrepreneurship, specifically physical infrastructure, networking, financial support, business assistance, and enabling environment services. The information was gathered from business incubators. Descriptive analysis and frequencies were used in the analysis. According to empirical findings, all services have a favorable impact on entrepreneurship. The findings of this study will be useful for researchers, policymakers, and others.